Outcomes of Infectious versus Sterile Perforated Corneal Ulcers after Therapeutic Penetrating Keratoplasty in the United States - Sloan W. Rush; Ryan B. Rush (Journal of Ophthalmology)
Purpose. To compare the long-term outcomes of infectious versus sterile perforated corneal ulcers after therapeutic penetrating keratoplasty in the United States. Methods. The charts of 45 consecutive eyes that underwent primary therapeutic penetrating keratoplasty for a perforated corneal ulcer at a single center were retrospectively reviewed. The perforated ulcers were classified as infectious or sterile and the underlying demographics, clinical features, and 36-month outcomes were compared among the two groups. Results. Mean follow-up among subjects was 38.6 (±6.9) months. Patients presenting with sterile perforated ulcers were more likely to have a peripheral perforation location (p=0.0333) and recurrence of the underlying disease condition (p=0.0321), require adjunctive surgical measures in the immediate postoperative period (p<0.0001), have reperforation after keratoplasty (p=0.0079), have worse best corrected visual acuity (p=0.0130), develop no light perception vision (p=0.0053), and require enucleation/evisceration (p=0.0252) when compared to the infectious perforated ulcer group. Conclusions. Sterile perforated corneal ulcers have a worse prognosis and may be more frequent than those caused by infectious disease in the United States compared to the developing world.